Separate School Placement for Students With Extensive Support Needs and the Potential Impact of Locale and Charter School Enrollment - Jessica A Bowman; Yi-Chen Wu
Separate school placements persist for students with extensive support needs (ESN) despite longstanding federal mandates for all students with disabilities to be educated in the least restrictive environment. This study extends research on separate school placement for students with ESN to explore the potential impact of locale and charter school policy by determining (1) the percentage of separate schools in states across locales, (2) whether there is a relationship between the percentages of separate schools in each locale and separate school placement rates, and (3) how the number and location of separate special education charter schools change by state over time. Results showed varying proportions of separate schools among each locale in states with different placement rates, a significant moderate difference between the percentage of separate schools in suburban locales and overall separate school placement rate, and few separate special education charter schools. Implications for research and practice are highlighted.